Prophecy and public affairs in later medieval England - Coote, Lesley A. (Lesley Ann), 1954- (Woodbridge, Suffolk ; Rochester, NY : York Medieval Press in association with Boydell Press, 2000)
In the first general survey of political prophecy in medieval England for almost a hundred years, Lesley Coote examines the nature of political prophecy, its audience and its reception, from its emergence in the twelfth century to the end of the middle ages. Working from original manuscripts, she reveals prophecy to have been a major language for the discussion of public affairs, enshrining ideas of 'Englishness' and a 'national' community, and introducing a great crusading hero-ruler, a second Arthur, who would lead his people into the Last Days.
Preliminaries; Contents; Acknowledgements; Abbreviations; Introduction; 1 What is Political Prophecy?; 2 The Second Arthur: The King as hero c. 1135-1307; 3 Expectation and Disappointment 1307-1340; 4 Debate and Crusade 1340-1399; 5 The Imperial Hero 1399-1440; 6 Cadwallader and the Angelic Voice: The Rationalization of Chaos 1450"1485; Postscript; Handlist of Manuscripts; Bibliography; Index.
Includes bibliographical references (pages 281-296) and index.
"Handlist of manuscripts": pages 239-280
Print version record.
JSTOR
Keywords: English literature -- Middle English, 1100-1500 -- History and criticism; Politics and literature -- Great Britain -- History -- To 1500.; Great Britain -- Politics and government -- 1154-1399.; Great Britain -- Politics and government -- 1399-1485.; National characteristics, English, in literature; Public opinion -- England -- History -- To 1500.; Arthurian romances -- Appreciation -- England; Nationalism -- England -- History -- To 1500.; Great Britain -- History -- Prophecies; Nationalism in literature; Prophecies in literature; Prophecy in literature; Heroes in literature; Littérature anglaise -- 1100-1500 (Moyen anglais) -- Histoire et critique; Grande-Bretagne -- Politique et gouvernement -- 1154-1399.; Grande-Bretagne -- Politique et gouvernement -- 1399-1485.; Anglais dans la littérature.; Cycle d'Arthur -- Appréciation -- Angleterre; Grande-Bretagne -- Histoire -- Prophéties.; Nationalisme dans la littérature.; Prophéties dans la littérature.; Prophétie dans la littérature.; Héros dans la littérature.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Arthurian romances -- Appreciation; English literature -- Middle English; Heroes in literature; National characteristics, English, in literature; Nationalism; Nationalism in literature; Politics and government; Politics and literature; Prophecies in literature; Prophecy in literature; Public opinion; England; Great Britain; To 1500; Electronic books; Prophecies; Criticism, interpretation, etc; History